Relative Preservation of Superior Semicircular Canal Architecture in CHARGE Syndrome. (June 2019) - Tawfik, Kareem O.; Leader, Brittany A.; Walters, Zoe A.; Choo, Daniel I.
Objectives: (1) Describe common patterns of semicircular canal (SCC) anomalies in CHARGE syndrome (CS) and (2) recognize that in CS, the architecture of the superior SCC may be relatively preserved. Study Design: This is a retrospective review of temporal bone imaging studies. Setting: Quaternary care center. Subjects and Methods: A sample of 37 patients with CS. All subjects met clinical diagnostic criteria for CS. The presence/absence of anomalies of the middle ear, mastoid, temporal bone venous anatomy, inner ear, and internal auditory canal was recorded. Anomalies of each SCC were considered separately and by severity (normal, dysplasia, aplasia). Results: Thirty-seven subjects (74 temporal bones) were reviewed. Thirty-four (92.0%) patients demonstrated bilateral SCC anomalies. Three (8.0%) had normal SCCs. In patients with SCC anomalies, all canals demonstrated bilateral abnormalities. Thirty-two (86.5%) patients had bilateral horizontal SCC aplasia. These 32 patients also demonstrated posterior SCC aplasia in at least 1 ear. Of 74 temporal bones, 37 (50.0%) had superior SCC dysplasia. All dysplastic superior SCCs showed preservation of the anterior limb. Complete superior SCC aplasia was found in 28 (37.8%) temporal bones. Conclusion: SCC anomalies occur with high frequency in CS. Complete absence of the horizontal and posterior canals is typical and usually bilateral. By contrast, the superior SCC often demonstrates relative preservation of the anterior limb.